Synthesis of Cyclopenta[b]Benzo[g][1,8]Naphthyridines - Arul Prakash, G.; Sampath Kumar, N.; Rajendran, S.P. (Asian Journal of Chemistry, 2010)
2-Chloro-3-formylquinoline 1 and its derivatives were prepared and aminated by dry ammonia gas in ethanol. The 2-amino-3-formylquinolines 2 so obtained were then condensed with cyclopentanone in presence of acetic acid and sulphuric acid to give benzo[g]cyclopenta[b][1,8]naphthyridines 3.